Growth of superior Turkish red pine (Pinus brutia Ten.) provenances - Ali Cem Aydın; Alper Ahmet Özbey; Mehmet Çalıkoğlu (Turkish Journal of Forestry, 2022)
In this study, the response rate of provenance trial efforts was estimated in terms of tree growth in Turkish red pine plantations. Investigations were executed at six different Pinus brutia provenance trials in Western Mediterranean Region of Turkey according to breast height diameter (dbh) at the end of the 30th year. Trials were established in randomized complete block design with 3 replications. In two best provenances according to dbh in each site, two trees nearest to plot mean in each block were cut and divided into one-meter stem sections. 5 years values of dbh over bark, dbh inside bark and basal area were calculated by stem analyses. Tree heights by ISSA method and stem volumes by Smalian Formula were estimated for same years. Growth of each characteristics over the years was compared with guide curves of site indexes in the Pinus brutia plantation yield table. As a result, in this study, the growth performances of the afforestations made by selecting superior provenances, according to the site classification of the existing Turkish red pine plantations were revealed.